PERAN BADAN PERMUSYAWARATAN DESA DALAM PENGAWASAN PENYELENGGARAAN PEMERINTAHAN DESA DI DESA MELATI II KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Dian Haryani (Universitas Medan Area, 2016)
This study examines the role How Village Consultative Body (BPD) in the supervision penyelengggaraan village government. This study aims to determine how the role of the Village Consultative Body under the supervision of village governance. This research uses qualitative research with descriptive nature of other research. Data collection methods used were 1) interview, 2) documentation, 3) observation. These results indicate that the Village Consultative Body on Jasmine Village II District Serdang Bedagai Perbaungan less instrumental in performing its oversight function.